2014
DOI: 10.1387/ijdb.140024jt
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of NUAK1 and NUAK2 expression during early chick development reveals specific patterns in the developing head

Abstract: Several human diseases are associated with the NUAK1 and NUAK2 genes. These genes encode kinases, members of the AMPK-related kinases (ARK) gene family. Both NUAK1 and NUAK2 are known targets of the serine threonine kinase LKB1, a tumor suppressor involved in regulating cell polarity. While much is known about their functions in disease, their expression pattern in normal development has not been extensively studied. Here, we present the expression patterns for NUAK1 and NUAK2 in the chick during early-stage e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…NUAK2 encodes an SNF1/AMPK-related kinase (also known as SNARK), which is often amplified in human cancers ( Namiki et al, 2011 ; Sun et al, 2013 ). In animal studies, it was shown that Nuak2 is specifically expressed in neural folds of the nascent head of chick and mouse embryos ( Bekri et al, 2014 ; Hirano et al, 2006 ; Ohmura et al, 2012 ). Local deficit or accumulation of Nuak2 mRNA in chick neural folds correlated with the curvature direction of the neuroectoderm at the median hinge point and dorsolateral hinge point ( Bekri et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NUAK2 encodes an SNF1/AMPK-related kinase (also known as SNARK), which is often amplified in human cancers ( Namiki et al, 2011 ; Sun et al, 2013 ). In animal studies, it was shown that Nuak2 is specifically expressed in neural folds of the nascent head of chick and mouse embryos ( Bekri et al, 2014 ; Hirano et al, 2006 ; Ohmura et al, 2012 ). Local deficit or accumulation of Nuak2 mRNA in chick neural folds correlated with the curvature direction of the neuroectoderm at the median hinge point and dorsolateral hinge point ( Bekri et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…In animal studies, it was shown that Nuak2 is specifically expressed in neural folds of the nascent head of chick and mouse embryos ( Bekri et al, 2014 ; Hirano et al, 2006 ; Ohmura et al, 2012 ). Local deficit or accumulation of Nuak2 mRNA in chick neural folds correlated with the curvature direction of the neuroectoderm at the median hinge point and dorsolateral hinge point ( Bekri et al, 2014 ). Importantly, Nuak2 knockout mice show NTDs including exencephaly in 40% of live births, which lends strong support for a potential role for this kinase during NTC in mammals ( Ohmura et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…The embryos were then hydrated by inverted gradients and loaded into sample holders and mounted into an in situ hybridization device (Folgentec-France). Embryos were subjected for 22 h to a continuous stream (1.7 ml/min) of successive reagents following the in situ hybridization protocol as previously described (Bekri et al, 2014 ). Finally, enzymatic detection was performed in PM purple reagent (Roche) under constant observation.…”
Section: Methodsmentioning
confidence: 99%
“…This kinase is highly expressed early in the developing brain and in microglia (Figure 3). 79 NUAK1 was reported as a biomarker for AD in a GWAS (Table 1). Through assessment of Aβ levels in vivo via PET imaging, NUAK1 was associated with quantitative global Aβ loading.…”
Section: New Targets and Preclinical Candidates For Ad Pd And Alsmentioning
confidence: 99%